Application of microcatheter shaping based on computational fluid dynamics simulation of cerebral blood flow in the intervention of posterior communicating aneurysm of the internal carotid artery - Xu, Gangqin; Ba, Yueyang; Zhang, Kun; Cai, Dongyang; Yang, Bowen; Zhao, Tongyuan; Xue, Jiangyu (Frontiers in Neurology, 2023)
Introduction The present study aimed to investigate the application of the aneurysm embolization microcatheter plasticity method based on computational fluid dynamics (CFD) to simulate cerebral blood flow in the interventional treatment of posterior communicating aneurysms in the internal carotid artery and to evaluate its practicality and safety. Methods A total of 20 patients with posterior internal carotid artery communicating aneurysms who used CFD to simulate cerebral flow lines from January 2020 to December 2022 in our hospital were analyzed. Microcatheter shaping and interventional embolization were performed according to the main cerebral flow lines, and the success rate, stability, and effect of the microcatheter being in place were analyzed. Results Among the 20 patients, the microcatheters were all smoothly placed and the catheters were stable during the in vitro model test. In addition, the microcatheters were all smoothly placed during the operation, with a success rate of 100%. The catheter tips were stable and well-supported intraoperatively, and no catheter prolapse was registered. The aneurysm was completely embolized in 19 cases immediately after surgery, and a small amount of the aneurysm neck remained in one case. There were no intraoperative complications related to the embolization catheter operation. Conclusion Microcatheter shaping based on CFD simulation of cerebral blood flow, with precise catheter shaping, leads to a high success rate in catheter placing, stability, and good support, and greatly reduces the difficulty of catheter shaping. This catheter-shaping method is worthy of further study and exploration.